STRATEGI MENINGKATKAN KEMAMPUAN MEMBACA ALQURAN MELALUI PROGRAM TAMENG (TADARUS DAN MENGAJI) DI MIN 1 JOMBANG - Muna * waroh (LP2M IAIN Tulungagung, 2020)
Abstrac: Learning the Koran becomes a very important part for elementary level children, various methods and methods are used to deliver children able to read the Koran fluently. One of the methods used in practicing the ability to read the quran in elementary school level is Ummi which is packaged in the form of a tadarus program and reciting (Shielding) as a strategy for children to be proficient in reading the Koran. This method gives an extraordinary impact on the ability to read the Quran even to memorize. Learning the Koran is certainly not limited by age, but giving the Koran teaching from an early age would be very important to equip children in its development in the future. Kata kunci: Strategi, Membaca Alquran, Program Tameng